Government Health Spending and Life Expectancy: Evidence from Cities and Districts in Indonesia - Sari, Kurnia; Hidayat, Budi; Sjaaf, Amal Chalik; Nadjib, Mardiati (Kesmas, 2025)
Life expectancy is widely recognized as a fundamental indicator of population health, and its improvement is often linked to government health spending, particularly in decentralized health systems. This study aimed to investigate the relationship between local government health expenditures and life expectancy in decentralized Indonesia. Data from 492 cities and districts, spanning from 2015 to 2019, were analyzed using a two-way fixed effects regression model to control for time-invariant district characteristics and common temporal shocks. The findings indicated that a 10% increase per capita in government health expenditure was associated with a 0.01% increase in life expectancy. This association was established after adjusting for key health system and contextual variables, including physician density, sanitation coverage, poverty rates, and proportion of fiscal transfers from the central government. The association remained strong and statistically significant across all model parameters. The results demonstrated that increased local health expenditure improves population health outcomes.